IMPLEMENTASI KEBIJAKAN MERDEKA BELAJAR KAMPUS MERDEKA PADA PERGURUAN TINGGI: (Studi pada Fakultas Vokasi Universitas Brawijaya) - Chelsie Enda Putri (Jurnal Administrasi Publik, 2023)
The new policy from the Ministry of Education and Culture is Freedom to Learn on an Independent Campus (MBKM). This policy allows students to complete three semesters outside of the student study program. This article discusses the implementation of the MBKM policy at the Faculty of Vocational Studies, Universitas Brawijaya (FV-UB). 1) Communication that occurs between universities, faculties, and students so far uses indirect communication methods because they are more effective and efficient. However, direct communication is also used. 2) Adequate resources and support for the implementation of the MBKM policy at FV-UB include human resources, budgetary resources, information and authority, and infrastructure. 3) Disposition is determined based on the compliance level of policy implementers and students. Because of their positive attitude towards the MBKM policy, the compliance of policy implementers is considered very good. 4) Based on the availability of SOPs related to the implementation of the MBKM policy in FV-UB and fragmentation, the bureaucratic structure has a pattern of working relationships that are very good and consistent with their respective fields.